Sustainable Marketing Orientation, Consumer Trust, and Sustainability Performance: Empirical Evidence from the Organic Vegetable Market - Walter Tabelessy (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to examine the impact of sustainable marketing orientation on sustainable performance among organic vegetable producers in Ambon City, focusing on consumer trust as a variable that acts as a partial mediator. A total of 175 respondents were selected using purposive sampling to become the sample in this study. To analyze the data, the SEM-PLS technique was used through the ADANCO application to test the relationship between variables. The results of this study indicate that a sustainable marketing orientation has a significant positive effect on sustainable performance and consumer trust. Consumer trust acts as a partial mediator, strengthening the relationship between sustainable marketing orientation and sustainable performance. This finding underscores the importance of implementing sustainability-focused marketing strategies in creating long-term value for companies, while building closer and more sustainable relationships with consumers.